Scoping review of propelling aids for manual wheelchairs. Issue 2 (4th March 2021) - Choukou, Mohamed-Amine; Best, Krista L.; Potvin-Gilbert, Maude; Routhier, François; Lettre, Josiane; Gamache, Stéphanie; Borisoff, Jaimie F.; Gagnon, Dany
ABSTRACT: Manual wheelchair (MWC) users face a variety of obstacles limiting their participation. Different MWC models and new add-on components intended to improve propulsion may impact users' function and participation, although there is a lack of research on this topic. The aims of this study were to: 1) identify MWC propelling aids (PA) that are reported in the literature; 2) classify the outcomes used to evaluate the influence of PA according to the International Classification of Functioning, Disability and Health (ICF); and 3) summarize evidence for the influence of PA. A scoping review was conducted in 2017 using Pubmed, Medline, Embase, CINAHL, Compendex, IEEE Xplore, RESNA and ISS proceedings, Google, and Google Scholar. The content of each manuscript was assessed by two independent reviewers. A total of 28 PA (19 human-powered; 9 power-assisted) were identified from 163 manuscripts. The three most cited ICF subdomains were "Activity & Participation" ( n = 125), "Body Function" ( n = 100), and "Personal Factors" ( n = 55). The findings suggest an overall positive influence of PA on various ICF domains/subdomains, but initial findings should be interpreted with caution. Confirmation of the effect and safety of PA requires higher levels of evidence.